The Strategy of Islamic Religious Education Teachers in Instilling Islamic Character During the Covid-19 Pandemic Period - Burhanudin Ata Gusman; Hanif Cahyo Adi Kistoro; Sutipyo Ru’iya (Al Qalam, 2021)
The COVID-19 pandemic has had an impact on many aspects, one of which is the education aspect. Currently, the affective element is the main focus for educators. This study aims to determine the system, approach, and impact of the teacher's strategy. This research is qualitative research with a phenomenological approach. The research subjects were research informants, namely teachers, school principals, and ten students—methods of data collection using interviews with interview guide instruments prepared. This study found three crucial points: the system or strategy for planting the character of the teacher's approach and the impact of growing Islamic symbols. The process of Islamic religious education teachers in character building is through three ways, namely exemplary, advice and habituation. The positive impact that occurs is that students at MAN 4 Kebumen have implemented the planting of Islamic characters given by the teacher so that students experience changes in terms of nature such as behavior Changes include students helping each other, doing assignments on time, diligence in worship, accustomed to reading prayers, and eager to learn. Keywords: Strategy; Islamic character; Example; Advice; Habit.